BREXİT'İN EKONOMİK YANSIMALARI: AVRUPA ÜLKELERİNDE MAKROEKONOMİK KARŞILAŞTIRMALI BİR DEĞERLENDİRME - Durğun, Hasan (Kütahya Dumlupinar University, 2025)
Bu çalışma, Brexit’in Almanya, Fransa, Hollanda, Belçika, İtalya, İspanya ve Portekiz ekonomileri üzerindeki etkilerini karşılaştırmalı olarak analiz etmektedir. G7’nin Avrupa’daki temsilcileri (G7-EU) için Brexit öncesi (2013-2015) ve sonrası (2017-2019) dönemler, betimsel istatistik yöntemiyle incelenmiştir. Büyüme, işsizlik, dış ticaret ve kamu borcu gibi göstergeler değerlendirilmiş, bulgular Brexit’in Avrupa ekonomileri üzerindeki etkisinin ülkelere göre farklılaştığını ortaya çıkarmıştır. Çalışma, Brexit sonrası ekonomik dinamikleri anlamaya katkı sağlarken, AB ülkeleri için karşılaştırmalı bir perspektif sunarak literatüre karşılaştırmalı bir perspektif sunmaktadır.

Brexit has led to economic fluctuations across European Union countries. This study conducts a comparative analysis of the impact of Brexit on the economies of Germany, France, the Netherlands, Belgium, Italy, Spain, and Portugal. Using descriptive statistical methods, the study examines the pre-Brexit (2013–2015) and post-Brexit (2017–2019) periods for the European representatives of the G7 (G7-EU). Key macroeconomic indicators such as growth, unemployment, trade balance, and public debt are evaluated, revealing that the economic effects of Brexit vary across countries. By contributing to the understanding of post-Brexit economic dynamics, this study provides a comparative perspective on the economic consequences for EU countries, offering a significant addition to the literature.
The Economic Implications of Brexit: A Comparative Macroeconomic Assessment of European Countries
Keywords: Macroeconomics (Other); Makro İktisat (Diğer) Political Economy; Politik Ekonomi European Union Economy; Avrupa Birliği Ekonomisi International Economics (Other); Uluslararası İktisat (Diğer)